Erciyes Clinical Guideline For Multisystem Inflammatory Syndrome In Children (MIS-C) Associated With COVID-19 - Benhur Sirvan Cetin; Ayşenur Paç Kısaarslan; Ali Baykan; Başak Nur Akyıldız; Hakan Poyrazoglu (The Journal of Pediatric Academy, 2022)
Multisystem Inflammatory Syndrome in Children (MIS-C) is an inflammatory response to prior SARS-CoV-2 infection. Clinical features of MIS-C could resemble those seen in other diseases, including Kawasaki Disease, Hemophagocytic Lymphohistiocytosis, and cardiovascular shock. The pathogenesis is unclear; however, it is thought to develop 4 to 6 weeks after infection. This guideline aims to provide a framework for physicians to use to guide the evaluation of patients and management of those diagnosed with MIS-C.